2014
DOI: 10.1007/s11655-014-1746-1
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of dimethyl dimethoxy biphenyl dicarboxylate on collagen-induced arthritis in rats

Abstract: Our data shed light on the therapeutic efficacy of DDB in experimental rheumatoid arthritis (RA) compared with a choice drug (MTX) and it may be offered as a second-line drug in the treatment of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The CIA-induced animal model was employed for the present study, as CIA may alter cellular and humoral immunity and thus mimic the human RA condition. Previous studies have demonstrated that attenuation of the CIA-induced inflammatory process in rats is among the best methods to assess the anti-RA activity of a drug (24,25). Paw swelling (edema) and arthritis scores are the most important factors to consider when examining the anti-inflammatory and anti-arthritic properties of a drug (26).…”
Section: Discussionmentioning
confidence: 99%
“…The CIA-induced animal model was employed for the present study, as CIA may alter cellular and humoral immunity and thus mimic the human RA condition. Previous studies have demonstrated that attenuation of the CIA-induced inflammatory process in rats is among the best methods to assess the anti-RA activity of a drug (24,25). Paw swelling (edema) and arthritis scores are the most important factors to consider when examining the anti-inflammatory and anti-arthritic properties of a drug (26).…”
Section: Discussionmentioning
confidence: 99%
“…On day 0, rats were injected intradermally at the tail base with 200 μL of a collagen‐II and IFA emulsion. Seven days after the initial immunization (day 0), rats received a booster injection on the other side of the tail with 100 μL of the emulsion to ensure a high incidence and severity of arthritis 58 . The CIA rats were then divided into 5 groups (groups 2‐6; 10 rats/group) as follows: group 2, CIA group without any treatment; group 3, MTX‐treated (rats received 4 intra‐peritoneal injections of MTX (1 mg/kg) as described by Hou et al 59 on days 11, 17, 24 and 31); and group 4, infliximab‐treated (rats were intravenously injected with 7 mg/kg as described by Smolen et al 60 on day 11).…”
Section: Methodsmentioning
confidence: 99%